Hubungan Sikap dengan Minat Ibu Hamil dalam Mengikuti Program Vaksinasi Covid-19 - Asri Basselo; Andi Nilawati Usman; Mardiana Ahmad; Deviana Soraya Riu; Budu Budu; Healthy Hidayanti (Malahayati Nursing Journal, 2023)
ABSTRACT Getting vaccinated during pregnancy will prevent pregnant women from having severe symptoms if exposed to Covid-19. However, there are still concerns from the public, especially pregnant women, about the side effects or impact of vaccines on vaccine recipients which has an impact on the low acceptance or interest of pregnant women in getting vaccinated against Covid-19. The purpose of this study was to analyze the relationship between attitudes and pregnant women's interest in participating in the Covid-19 vaccination program at the Sowi Community Health Center, Manokwari Regency. This type of research is an analytic research with a cross-sectional study approach in which the independent variables and the dependent variables are measured at the same time. The researcher only made observations without intervening in the research subjects. The sample in this study were all second and third trimester pregnant women who visited the Sowi Health Center using a total sampling technique. This study uses human research subjects, namely as many as 77 respondents who will be given a questionnaire that has been tested for validity and reliability. The data taken is primary data and data analysis using the Chi-Square test. The results showed that there was no relationship between attitude and the interest of pregnant women in participating in the Covid-19 vaccination program at the Sowi Community Health Center, Manokwari Regency, with a p value α value (0.05). The conclusion is that the attitude of pregnant women is not a factor that can influence the interest of pregnant women to take part in the Covid-19 vaccination program. Keywords: Covid-19 Vaccination, Attitude, Interests of Pregnant Women  ABSTRAK Mendapatkan vaksinasi dalam masa kehamilan akan mencegah ibu hamil bergejala berat bila terpapar Covid-19 namun masih ada kekhawatiran masyarakat terutama ibu hamil tentang efek samping atau dampak vaksin terhadap para penerima vaksin yang berdampak pada rendahnya penerimaan atau minat ibu hamil terhadap vaksinasi Covid-19. Tujuan dari penelitian ini adalah untuk menganalisis hubungan sikap dengan minat ibu hamil dalam mengikuti program vaksinasi covid-19 di Puskesmas Sowi Kabupaten Manokwari. Jenis penelitian ini merupakan penelitian analitik dengan pendekatan cross-sectional study  dimana variabel independen dan variabel dependen diukur pada waktu yang bersamaan. Peneliti hanya melakukan observasi tanpa melakukan intervensi terhadap subjek penelitian Sampel dalam penelitian ini adalah semua ibu hamil trimester II dan III yang berkunjung ke Puskesmas Sowi dengan teknik total sampling. Penelitian ini menggunakan subjek penelitian manusia yaitu sebanyak 77 responden yang akan diberikan kuisioner yang telah diuji validitas dan reliabilitas. Data yang diambil merupakan data primer dan analisa data menggunakan uji Chi-Square. Hasil penelitian menunjukan bahwa tidak terdapat hubungan sikap dengan minat ibu hamil dalam mengikuti program vaksinasi covid-19 di Puskesmas Sowi Kabupaten Manokwari dengan nilai p value nilai α (0,05). Kesimpulan yaitu sikap ibu hamil bukan merupakan faktor yang dapat mempengaruhi minat ibu hamil untuk mengikuti program vaksinasi Covid-19. Kata Kunci : Vaksinasi Covid-19, Sikap, Minat Ibu Hamil